(untitled) (Academic Journal of Internal Affairs, 2015)
The book is a comprehensive discussion of the subject, a multidisciplinary monograph due to its multidisciplinary nature and systems approach. It brings its reader to a complex, new perspective, thus undoubtedly bringing him closer to the optimal treatment and “solution” of a living social phenomenon.